Changing trends in corneal graft surgery: a ten-year review - Ugo de Sanctis; Camilla Alovisi; Luigi Bauchiero; Guido Caramello; Gianfranco Girotto; Claudio Panico; Luisa Vinai; Federico Genzano; Antonio Amoroso; Federico Grignolo (International Journal of Ophthalmology, 2016)
AIM: To review indications and corneal tissue use for penetrating and lamellar surgery between 2002 and 2011. METHODS: The surgical reports of corneal grafts performed during 2002-2011, using tissues supplied by the Eye Bank of Piedmont (Italy), were reviewed retrospectively. Patient demographic data, date of intervention, indication for surgery, and surgical technique used were recorded. Surgical techniques included penetrating keratoplasty (PK), deep anterior lamellar keratoplasty (DALK) and endothelial keratoplasty (EK). The χ2 test was used to compare the distribution of indications and types of surgical technique used, for corneal grafts done during 2002-2006 versus those done during 2007-2011. RESULTS: The number of corneal grafts increased by 30.7% from 2002-2006 to 2007-2011 (from 1567 to 2048). Comparing the two periods, both main indications and surgical techniques changed significantly. In 2007-2011, the proportion of interventions for aphakic/pseudophakic bullous keratopathy (from 16.8% to 21.3%), graft failure (from 16.4% to 19.1%) and Fuchs endothelial dystrophy (from 12.8% to 16.7%) all increased significantly (P<0.05), while those for keratoconus decreased significantly (from 35.6% to 27.3%; P<0.001). In 2007-2011, the proportion of PK decreased significantly (from 92.4% to 57.2%; P<0.001) while that of EK and DALK went from 0.4% to 30.2% (P<0.001) and from 7.2% to 12.6% (P<0.001) respectively. CONCLUSION: During 2002-2011 the number of interventions increased significantly for corneal endothelial diseases and graft failure. The growing demand for interventions for these diseases corresponded to the widespread adoption of EK techniques. The use of DALK also increased, but more moderately than EK procedures.